2019
DOI: 10.1111/flan.12373
|View full text |Cite
|
Sign up to set email alerts
|

Facing reality: A survey of methods instructors’ perspectives on world language teacher development

Abstract: This study reports the findings of a national survey on PreK–12 world language teacher development (WLTD), and was conducted in order to assist the profession as simultaneously it confronts the intersecting challenges of a nationwide world language (WL) teacher shortage, strives to meet new teacher preparation standards, and ensures the future of language teaching and learning in American schools. The 164 methods instructors (MIs) described the contexts in which they address pre‐service candidates' needs and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 37 publications
0
26
0
1
Order By: Relevance
“…Approximately three‐fourths of all CTs were over the age of 40, with 36.2% between the ages of 51 and 60. One significant issue for consideration is the impact of CT retirement on PreK–12 WL programs in light of two challenges: (a) the established WL teacher shortage (Swanson, ) and (b) the precarious status of WL teacher education programs due to budget constraints and low enrollment (García et al, ). As WL CTs retire, who will work with the next, increasingly small number of TCs who plan to enter tomorrow's WL classrooms and teach our PreK–12 learners?…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Approximately three‐fourths of all CTs were over the age of 40, with 36.2% between the ages of 51 and 60. One significant issue for consideration is the impact of CT retirement on PreK–12 WL programs in light of two challenges: (a) the established WL teacher shortage (Swanson, ) and (b) the precarious status of WL teacher education programs due to budget constraints and low enrollment (García et al, ). As WL CTs retire, who will work with the next, increasingly small number of TCs who plan to enter tomorrow's WL classrooms and teach our PreK–12 learners?…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it may be easier to assign TCs to secondary‐level placements due to the limited availability of PreK–5 settings and programs. While scholars (García et al, ; Hoyt & Terantino, ) have routinely suggested the purposeful selection of CTs based on qualifications, Russell and Davidson Devall () argued that the limited supply of CTs makes it difficult to enact such a practice. Given the established influence of CTs on TC practice both during and following the practicum—confirmed by Behney's () finding that “teacher candidates expressed concern that the placement and choice of their CT could potentially advantage some candidates while making it more challenging for others to meet expectations” (pp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations